Dopamine antagonists for the treatment of drug addiction: PF-4363467 and related compounds - Martinez, Ana (European Journal of Chemistry, 2020)
Drug addiction refers to an out-of-control and compulsive use of substances, which can reach epidemic magnitudes. It is a health concern throughout the world and has major economic impact. Dopamine receptor agonists and antagonists have been cited as molecular targets for the treatment of drug addiction. In this report, the main idea is to analyze the new D3R/D2R ligands that are proposed for the treatment of drug abuse, in terms of their electron donor/acceptor properties. Substances catalogued as agonists represent good electron donors, whereas antagonists represent good electron acceptors. HOMO and LUMO eigenvalues indicate that more energy is necessary to remove an electron from the antagonists, and likewise more energy is gained when antagonists accept an electron. The combination of two molecules (PF-592379 and PNU-177864) produces a new compound (PF-4363467) with properties that are intermediate. Irrespective of the characteristics of the receptor, the classification of ligands is important, in order to further understanding of the reaction mechanism of these compounds. This may help in the design of new molecules for the treatment of drug addiction.